Quantification of neurological blood‐based biomarkers in critically ill patients with COVID‐19: Developing topics. (7th December 2020) - Cooper, Jennifer; Stukas, Sophie K; Hoiland, Ryan; Thiara, Sonny; Foster, Denise; Mitra, Anish; Panenka, William J; Sekhon, Mypinder S; Wellington, Cheryl L
Abstract: Background: Multiple neurological manifestations of COVID‐19 have been reported such as headache, anosmia, ischemic stroke, and cerebral hemorrhages. Objective characterization of the acute neurological damage in critically ill patients with COVID‐19 has not yet been reported. Method: We performed a prospective observational study of plasma brain biomarkers in critically ill patients with respiratory failure that were diagnosed with (COVID‐19) or without (ICU control) COVID‐19. Demographics, co‐morbidities, daily clinical physiologic and laboratory data were collected. Plasma samples were drawn for measurement of neurofilament‐light chain (NF‐L), total tau (t‐tau), ubiquitin carboxy‐terminal hydrolase L1 (UCH‐L1), and glial fibrillary acidic protein (GFAP). The primary neurological outcome was delirium as defined by the intensive care delirium screening checklist (ICDSC, scale 1 ‐ 8). Associations between brain biomarkers and markers of respiratory failure of COVID‐19 were analyzed. Result: 27 patients with COVID‐19 and 19 ICU controls were enrolled. The concentration of plasma GFAP, UCH‐L1 and NF‐L levels was higher in both groups compared to healthy controls. Compared to ICU controls, patients with COVID‐19 had significantly higher GFAP (272 [150‐555] pg/ml vs 118 [78.5‐168] pg/ml, p=0.0009). In patients with COVID‐19, GFAP (rho=0.5115, p=0.0064), UCH‐L1 (rho=0.4056, p=0.0358) and NF‐L (rho=0.6223, p=0.0005) were positively correlated with the ICDSC score and were higher in patients diagnosed with delirium (ICDSC ≥4) in the COVID‐19 group but not ICU controls. There were no associations between PaO2/FiO2 or diagnosis of ARDS and plasma concentration of GFAP, t‐tau, UCH‐L1, or NF‐L in patients with COVID‐19. Conclusion: Plasma GFAP is 2‐fold higher in critically ill patients with COVID‐19 compared to ICU controls, and higher concentrations of GFAP, UCH‐L1 and NF‐L are associated with delirium specifically in patients with COVID‐19.